PENGARUH PERHATIAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA PADA SMA NEGERI 2 SAMPIT - Fatimah Setiani; Jayadi Jayadi; Sandra Setyaningsih (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
The purpose of this study was to determine the influence of parental attention to student learning motivation in the class XI IPA at SMA 2 Sampit in The Year of 2015/2016. Population in this study all students of grade XI IPA in SMA 2 Sampit as many as 195 students. The samples in this study was using the Simple Random Sampling technique with a sample size of 49 students. The research instrument using a questionnaire with Likert Scale. Test the validity using Product Moment Correlation formula, while the reability test in this study using the formula Coeffecient Alpha Cronbach. Technique of data analisys used is simple regression analisys and hypothesis test processed with SPSS for windows version 20. The results of research show that there is influence of parents attention to students motivation to study class XI IPA at SMA 2 Sampit in The Year of 2015/2016. The magnitude of the influence of parents attention to student learning motivation is 17% and the remaining 83% is obtained from other factors that can not be researched in this study.